Gender Equality Policy and Work Flexibility: Increasing Worker Self-Actualization Through a Multigroup Approach - Astri Mustakiah, Imas; Kania, Ikeu; Geusan Akbar, Gugun (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2025)
This research aims to examine the impact of gender equality and work flexibility on self-actualization in various groups of female workers through multigroup analysis and Importance-Performance Map Analysis (IPMA). The research method uses qualitative and quantitative approaches. Primary and secondary data were collected through direct observation, in-depth interviews, and literature reviews. The respondents for this research consisted of 200 women who worked in various sectors, with each occupational group represented by 20 individuals. The analysis method uses SmartPLS for quantitative data processing and NVIVO for qualitative data analysis. The research results show that work flexibility plays a significant role in supporting gender equality and women's self-actualization in their careers. These findings underscore the importance of more inclusive and effective work policies to improve the welfare and productivity of female workers. The sub-criteria of work flexibility and gender equality were identified as the main priorities in supporting self-actualization. Qualitative analysis with NVIVO strengthens the quantitative results by providing in-depth insights into the experiences and perceptions of female workers regarding work flexibility and gender equality. This research provides valuable insights for policymakers and practitioners in designing policies that are more responsive to the needs of female workers so that they can contribute to improving the overall welfare and productivity of the workforce.